Cracks, porosity and microstructure of Ti modified polymer-derived SiOC revealed by absorption-, XRD- and XRF-contrast 2D and 3D imaging. (1st October 2020) - Makowska, Małgorzata; Sasikumar, Pradeep Vallachira Warriam; Hagelüken, Lorenz; Sanchez, Dario F.; Casati, Nicola; Marone, Federica; Blugan, Gurdial; Brugger, Jürgen; Van Swygenhoven, Helena
Abstract: Morphology, phase composition, cracks and porosity are investigated in monolithic Ti modified SiOC polymer-derived ceramics pyrolyzed at 1000 °C and 1400 °C using synchrotron X-ray full field absorption-contrast tomographic microscopy and scanning XRF- and XRD-contrast microscopy. Samples pyrolyzed at 1000 °C show a crack-free structure, but pyrolysis at 1400 °C results in formation of cracks and at higher Ti content also shows porosity. Tomography revealed the formation of a layered morphology that varies in terms of crystallographic structure and/or Ti stoichiometric concentration. The microstructural observations and electrical conductivity are discussed in terms of pyrolysis temperature and Ti content. Graphical abstract: Image, graphical abstract